Investigation of heavy metal and radionuclide distribution in silt of lake Didžiulis - Butkus, Donatas; Šalčiūnienė, Kristina (Journal of Environmental Engineering and Landscape Management, 2011)
The article deals with research of the ecological situation in Lake Didžiulis, located nearby the highway Vilnius–Kaunas (Trakai District); the most polluted locations in the lake were identified. Research of heavy metals (HM) and radionuclides in the lake silt is described. To research HM concentrations and the specific activities of radionuclides, the samples were collected from 12 bores in the most typical locations of the lake. The estimated HM concentrations in the silt of Lake Didžiulis vary within a wide range: Cr from 6.9 to 45.2 mg/kg, Ni from 20.4 to 55.7 mg/kg, Mn from 236 to 1362 mg/kg, Cu from 7.1 to 80.9 mg/kg, Pb from 24.4 to 87.8 mg/kg, Zn from 13.0 to 75.8 mg/kg. The HM concentrations in the lake silt do not exceed the maximum allowed concentrations (MAC) in the soil, whereas the concentrations of manganese, copper and lead in some samples are close to MAC. The counted specific activities of 40K fluctuate from 46 Bq/kg to 415 Bq/kg in the upper level silt and from 125 Bq/kg to 482 Bq/kg in the silt, which is found near the mineral soil. The specific activities of other radionuclides at the said depths of the silt range as follows: 226Ra from 23 Bq/kg to 85 Bq/kg and from 28 Bq/kg to 93 Bq/kg, 227Ac from 2.1 Bq/kg to17.0 Bq/kg and from 7.3 Bq/kg to 23.0 Bq/kg, whereas artificial 137Cs from <0.6 Bq/kg to17.6 Bq/kg and from <0.5 Bq/kg to 12 Bq/kg. Article in English. Sunkiųjų metalų ir radionuklidų pasiskirstymo Didžiulio ežero dumble tyrimas Santrauka. Straipsnyje nagrinėjama Didžiulio ežero šalia greitkelio Vilnius – Kaunas (Trakų raj.) ekologinė būklė, nustatytos ežero vietos, kur buvusi didžiausia tarša. Aptariami atlikti sunkiųjų metalų (SM) bei radionuklidų koncentracijų ežero dumble tyrimai. SM koncentracijoms ir radionuklidų savitiesiems aktyvumams tirti ėminiai buvo imti iš 12 gręžinių, parinktų būdingiausiose ežero vietose. Didžiulio ežero dumble nustatytas gana platus SM koncentracijų intervalas: Cr – 6,9– 45,2 mg/kg, Ni – 20,4–55,7 mg/kg, Mn – 236–1362 mg/kg, Cu – 7,1–80,9 mg/kg, Pb – 24,4–87,8 mg/kg, Zn – 13,0– 75,8 mg/kg. SM koncentracijos ežero dumble neviršija didžiausių leidžiamųjų koncentracijų (DLK) dirvožemyje, tačiau kai kuriuose bandiniuose mangano, vario ir švino koncentracijos yra artimos DLK. Nustatytieji 40K savitieji aktyvumai svyruoja nuo 46 Bq/kg iki 415 Bq/kg paviršiniame dumble ir nuo 125 Bq/kg iki 482 Bq/kg esančiame arti mineralinio grunto. Kitų radionuklidų savitieji aktyvumai tuose dumblo gyliuose svyruoja taip: 226Ra – nuo 23 Bq/kg iki 85 Bq/kg ir nuo 28 Bq/kg iki 93 Bq/kg, 227Ac – nuo 2,1 Bq/kg iki 17,0 Bq/kg ir nuo 7,3 Bq/kg iki 23,0 Bq/kg, o dirbtinės kilmės 137Cs – nuo <0,6 Bq/kg iki 17,6 Bq/kg ir nuo <0,5 Bq/kg iki 12 Bq/kg. Reikšminiai žodžiai: ežero dumblas, Didžiulio ežeras, sunkieji metalai, radionuklidai. Исследование распределения тяжелых металлов и радионуклидов в иле озера «Диджулис» Резюме. Анализируется экологическoe состояние озера «Диджулис», которое находится возле магистральной дороги Вильнюс−Каунас (Тракайский район), идентифицируются места с наибольшим загрязнением, анализируютсярезультаты исследований тяжелых металлов (ТМ) и радионуклидов в иле. Для исследования концентраций ТМ испецифических активностей радионуклидов пробы ила были взяты из 12 скважин, подобранных в характерныхместах озера. Концентрации ТМ в иле озера «Диджулис» менялись в довольно широких интервалах: Cr – от6,9 мг/кг до 45,2 мг/кг, Ni − от 20,4 мг/кг до 55,7 мг/кг, Mn − от 236 мг/кг до 1362 мг/кг, Сu −от 7,1 мг/кг до 80,9 мг/кг, Pb − от 24,4 мг/кг до 87,8 мг/кг, Zn − от 13,0 мг/кг до 75,8 мг/кг. Концентрации ТМ, находящихся в илеозера, не превышали предельно допустимых концентраций (ПДК) в почве, однако в некоторых пробах концентрации марганца, меди и свинца были близки к ПДК. Специфическая активность 40K меняется от 46 Бк/кг до 415 Бк/кг на поверхности слоя ила и от 125 Бк/кг до 482 Бк/кг вблизи минерального грунта. Специфическиеактивности других радионуклидов на определенных глубинах ила меняются таким образом: 226Ra − от 23 Бк/кг до 85 Бк/кг и от 28 Бк/кг до 93 Бк/кг, 227Ac− от 2,1 Бк/кг до 17,0 Бк/кг и от 7,3 Бк/кг до 23,0 Бк/кг, а радионуклидов искусственного происхождения: 137Cs − от <0,6 Бк/кг до 17,6 Бк/кг и от < 0,5 Бк/кг до 12 Бк/кг. Ключевые слова: ил озера, озеро «Диджулис», тяжелые металлы, радионуклиды.